LIVING QURâ€˜AN DALAM TRADISI SELAWATAN DI MAJELIS SELAWAT AR-RIZQY CIREBON: Pendekatan Fenomenologi - Nela Safana Aufa; Muhammad Maimun; Didi Junaedi (UIN Siber Syekh Nurjati Cirebon, 2020)
The understanding of the Qurâ€™an produces a variety of cultural practices, which are the results of the reception of Muslims to the Qurâ€™an. One of them is the practice of reciting selawat which is carried out at Ar-Rizqy Selawat Majlis, Buntet Village, Astanajapura District, Cirebon Regency. It is the reception of QS. al-Aá¸¥zÃ¢b verse 56. There are two results of this study. The first one is that the background of the selawat tradition was a part of the practices of the QS. Al-Aá¸¥zabâ€™s command (verse 56). In addition, the recitation of the Qur'an as dhikr was believed to have strength or virtue. Another form of Living Qur'an practices was reciting the Qurâ€™an by reading it as much as one nisf (half of a juz), then reading QS al-FÃ¢tiá¸¥aá¸¥ once, and then reading QS al-IkhlÃ¢s, al-Falaq, al-NÃ¢s, and al-Kursiy Verse 70 times. The number of the counts (70) was based on the ijazah (certificate) given by the teacher. Besides, the number 70 is an odd number and Allah favors odd numbers. The second result is the reception to the Qur'an was a functional reception which consisted of 3 functions. The first function was to protect oneself from the disturbance by supernatural creatures. Qurâ€™anâ€™s verses considered as verses that could protect oneself from the disturbance by supernatural creatures were found in the sixth verse of QS al-NÃ¢s, the third verse of QS al-Falaq, and inÂ â€œya'lamu ma baina aidihim wa makhalfahumâ€ in al-Kursi. The second function was to use water as medicine. And the last one was to provide a psychological effect, namely to reassure the soul.Keywords: selawat tradition, reception and phenomenology.Â Pemahaman terhadap Alquran menghasilkan beragam perilaku kultural. Perilaku kultural merupakan hasil dari resepsi umat Islam terhadap al-Qurâ€™Ã¢n. Salah satu praktiknya ialah resepsi terhadap QS. al-Aá¸¥zab ayat 56 yakni praktik pembacaan selawat atau disebut dengan selawatan yang dilakukan di Majelis Selawat Ar-Rizqy Desa Buntet kecamatan Astanajapura, Kabupaten Cirebon. Hasil dari penulisan tersebut adalah pertama latar belakang tradisi selawatan bagian dari perilaku dari perintah QS. Al-Aá¸¥zab ayat 56 dan pembacaan Alquran dijadikan sebagai bacaan dzikir dipercaya memiliki kekuatan atau keutamaan. Bentuk praktik Living Qurâ€™an lainnya ialah pembacaan Alquran antara lain membaca Alquran sebanyak satu nishfu (setengah juz). Kemudian membaca surat al-FÃ¢tiá¸¥aá¸¥ 1 Kali, dan membaca surat al-IkhlÃ¢s, al-Falaq, an-NÃ¢s, dan ayat Kursi sebanyak 70 Kali. Banyaknya jumlah hitungan 70 kali berdasarkan hasil ijazah dari gurunya. Selain itu, angka 70 merupakan angka ganjil, dan Allah menyukai angka yang ganjil. Kedua, resepsi terhadap Alquran yaitu resepsi fungsional, 1) melindungi diri dari gangguan makhluk. Ayat Alquran yang dianggap sebagai ayat yang dapat melindungi diri dari gangguan makhluk menurut para pelaku ialah terdapat dalam ayat ke-6 surat an-NÃ¢s, ayat ke 3 surat al-Falaq dan pada lafaz yaâ€™lamu mÃ¢ bayna aydÃ®him wa mÃ¢ khalfahum dalam ayat kursi. 2) Penggunaan media air sebagai obat. 3) dapat memberikan efek psikologis yakni menentramkan jiwa.Kata Kunci: Tradisi selawatan, Resepsi dan Fenomenologi